PENERAPAN STRATEGI PEMBELAJARAN AKTIF FORMASI REGU TEMBAK (FIRING LINE) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LARUTAN PENYANGGA DI KELAS XI SMAN 10 PEKANBARU - Gurusinga, Evanita; Amran, Elva Yasmi; Rery, R. Usman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: This study aims to determine the improvement of student learning achievement and the influence of firing line active learning strategies on the subject matter of Buffer Solutions in class XI of SMAN 10 Pekanbaru. The form of this study is an experimental study using the Pretest-Posttest Design Randomized Control Group. The study sample consisted of 2 classes, namely class XI MIPA 1 as the experimental class and class XI MIPA 2 as the control class which had tested normality using the Liliefors test and tested homogeneity using two average similarity tests. The research hypothesis was tested using the right-t-test. The results showed that the application of active learning strategies for firing squad formation could improve student learning achievement on the subject of Buffer Solution with tcount = 3.78> table = 1.67 and the magnitude of the effect of increasing student achievement was categorized based on the N-Gain value of 0.75 which is included in the high category. It can be concluded that the application of active learning strategies for firing squad formation can improve students' learning achievement on the subject matter of buffer solution of class XI SMAN 10 Pekanbaru with the effect of an increase of 0.75.Key Words: Strategy for Shooting Squad (Firing Line), Learning Achievement, Buffer Solution.